LTE Network Area Coverage on FDD and TDD Technology - Chandra, Dikky; Yusnita, Sri; Sitepu, Dana Bahari; Mursydan, Arif; Meidelfi, Dwiny (SOTVI, 2020)
FDD (Frequency Division Duplexing) and TDD (Time Division Duplexing) Technology I is a duplex technology on the 4G LTE network. FDD technology in Indonesia is deployed in the 900 MHz, 1800 MHz and 2100 MHz frequency bands. Meanwhile, TDD technology uses frequency of 2300 MHz. In order to see the performance from the side of coverage, a measurement of the signal strength is conducted by direct measurements in field so that the appropriate technology and frequency band can be determined for the measurement area. The measurements have been done by two samples of different frequencies, namely 1800 MHz for FDD and 2300 MHz for TDD. Measurement of coverage is conducted on the same existing BTS and different BTS for both FDD and TDD modes. The parameter used in this measurement is the RSRQ value as one of the basic parameters of KPI (Key Performance Indicator). The results of drivetest data obtained the farthest coverage area of 789 m, namely the FDD (Frequency Division Duplexing) technology with frequency of 1800 MHz and TDD with frequency of 2300 MHz for 633 m.